A Novel Bond Anchor for Unidirectional FRP Member: Conceptual Design and Experimental Investigation - Yue Liu; Qing Wei; Ze-Yu Wang; Peng Xiang; Long-Ji Du; Bai-Yong Fu (Advances in Materials Science and Engineering)
Fiber-reinforced polymer (FRP) is an advanced composite material with many advantages including light weight, high strength, and high fatigue and corrosion resistance, which makes unidirectional FRP suitable for tension members, such as cables, prestressing tendons, and tie rods. However, the unidirectional FRP is a typical isotropic material, which is difficult to be anchored and hence unable to give full play to the advantages of FRP. To solve the anchoring problem of unidirectional FRP member, a novel bond anchor, i.e., dissolution-rebond anchor, is proposed in this paper. In this novel anchorage system, the polymer matrix of two ends of the unidirectional FRP member is dissolved by solvent and the fibers in the anchorage length are directly bonded by the binder. Theoretical analysis was performed to illustrate the high anchorage bearing capacity of this dissolution-rebond anchor. Static tensile test was conducted to verify this novel anchor design and compare with traditional bond anchor. Results show that the novel dissolution-rebond anchor is feasible and its anchorage efficiency is significantly higher than the traditional bond anchor.